A novel in situ synthesis of nitrogen-doped graphene with excellent electrocatalytic performance for oxygen reduction reaction. (1st June 2021) - Ou, Changrui; Chen, Hui; Wang, Hou; Liao, Yalin; Li, Run; Liu, Hongbo
Abstract: The heteroatom doped carbon-based materials have a promising application in fuel cell electrocatalysis. However, current metal-free catalyst always suffers drawbacks of slow dynamic rate and limited energy conversion efficiency. Here, nitrogen-doped graphene (N-G) with layered structure has been successfully in situ synthesized via magnesium reduction of graphitic carbon nitride (g-C3 N4 ) at 800 °C. Due to its excellent structure and properties including high BET surface area (437 m 2  g −1 ), plenty of graphitized nitrogen and pyridine nitrogen on the surface, and remarkable conductivity, the obtained 10N-G-800 demonstrates a prominent catalytic efficiency in electrocatalytic oxygen reduction reaction (ORR) via mainly four-electron pathway. In addition, an obviously better long-term catalytic stability and methanol tolerance than commercial platinum-carbon counterparts are also determined for our 10N-G-800 catalyst. The 10N-G-800 exhibits high power density (203 mW cm −2 ), long-term durability and high rate capacity as the air electrode catalyst of Zn-air battery. This article provides a novel and efficient approach for the design of metal-free ORR catalyst.